Natural selection, technological progress, and the origin of human longevity - Lothar Grall (Philipps-University Marburg, School of Business and Economics, 2016)
This paper suggests that feedback effects between technological progress and human longevity lie at the heart of their common emergence in human history. It connects two major research questions. First, the long life span after menopause is a unique but puzzling feature of humans among primates. Second, the shift in human behavior at least 50,000 years ago, which led to an unprecedented pace of technological progress, is still not well understood. The paper develops an evolutionary growth theory that builds on the trade-off between the quantity and the quality of offspring. It suggests that early technological advances gradually increased the importance of intergenerational transfers of knowledge. Eventually, the fertility advantage shifted towards individuals that were characterized by higher parental investment in offspring and a significant post-reproductive life span. Subsequently, the rise in human longevity reinforced the process of development and laid the foundations for sustained technological progress. As a key feature, the theory resolves the debate about a "revolution" in human behavior in an entirely new way. It shows that a gradual emergence of modern behavior is sufficient to trigger a demographic shift that appears as a "behavioral revolution" in the archeological record.
Keywords: J13; N30; O10; O30; 330; Behavioral Revolution; Economic Growth; Human Longevity; Natural Selection; Somatic Investment; Technological Progress